Thermodynamic Analysis for Binding of 4-O-β-tri-N-acetylchitotriosyl Moranoline, a Transition State Analogue Inhibitor for Hen Egg White Lysozyme - Ogata, Makoto; Fukamizo, Tamo; Ohnuma, Takayuki (Frontiers in Molecular Biosciences, 2021)
4-O-β-tri-N-acetylchitotriosyl moranoline (GN3M) is a transition-state analogue for hen egg white lysozyme (HEWL) and identified as the most potent inhibitor till date. Isothermal titration calorimetry experiments provided the thermodynamic parameters for binding of GN3M to HEWL and revealed that the binding is driven by a favorable enthalpy change (ΔH° = −11.0 kcal/mol) with an entropic penalty (−TΔS° = 2.6 kcal/mol), resulting in a free energy change (ΔG°) of −8.4 kcal/mol [Ogata et al. J. Biol. Chem. (2013) 288, 6072-6082]. Dissection of the entropic term showed that a favorable solvation entropy change (−TΔSsolv° = −9.2 kcal/mol) is its sole contributor. The change in heat capacity (ΔCp°) for the binding of GN3M was determined to be −120.2 cal/K·mol. These results indicate that the bound water molecules play a crucial role in the tight interaction between GN3M and HEWL.